THE RELATIONSHIP BETWEEN SELF DISCLOSURE AND HAPPINESS OF WORKING WIFE - Mariyanti, Sulis; Ayu Dinar, Diah; M, Safitri; Arwati, Dini (International Journal of Psychosocial Rehabilitation, 2020)
In carrying out the dual role as a housewife and work is not an easy thing. Various demands that must be carried out by working wives can cause fatigue, feelings of being burdened, and can even cause conflict in the household due to conflicting roles, thus making working wives unhappy. One of the things related to happiness is selfdisclosur . This study aims to determine the relationship between self-disclosure and happiness in working wives. This research is quantitative with a purposive sampling technique involving 100 respondents. The selfdisclosure measuring instrument used was compiled based on Wheeleess's self-disclosure theory totaling 34 valid items with a reliability value of 0.909, as well as a happiness measuring instrument compiled based on Seligman's happiness theory which amounted to 36 valid items with a reliability value of 0.914. Correlational test results obtained sig. (P) of 0.00 (p